PENGARUH UKURAN PERUSAHAAN, SOLVABILITAS, PROFITABILITAS, DAN UMUR PERUSAHAAN TERHADAP AUDIT REPORT LAG - Suryanti, Dewi Saptantinah Puji Astuti & Fadjar Harimurti (Universitas Slamet Riyadi, 2019)
The purpose of this research is to analyze the influence of the size of the company, solvency, profitability and the age of the company's of audit report lag. This is study an empirical study on the sector mining campanies listed in Indonesian Stock Exchange (IDX) periode 2014 - 2017. The data source uses secondary data. Study population is 41 company's auditors independent and a report form the 2014 - 2015 accessed wih IDX websites www.idx.co.id. The techniques sampling use a technique purposive sampling with the number of samples research as much a 28 company. The techniques collecting data using the documentation and study pustaka. The data analysis use of regressing linear berganda. The result of research suggests that the size of the company infliential positive towards of the audit report lag. Variable solvency problems doesn't effect positive toward of the audit report lag. Profitability influential negative against of the audit repoert lag. Age of the company has a negative effect significant against of the audit report lag. Keywords: the size of the company, solvency problems, the company's profitability, age of the audit report lag